Studi Potensial Korosi pada Sistem Proteksi Katodik Beton Bertulang Dengan Variasi Jarak Anoda - Syarizal Fonna; Syifaul Huzni; Muhammad Rizky (Jurnal Teknik Mesin Unsyiah, 2018)
The objective of this study is to study the influence of anode-cathode displacement to corrosion potential distribution of reinforced concrete cathodic protection system. Reinforced concrete speciments with a length of 1000 mm, width of 100 mm, and a height of 100 mm were used. Three variations of anode-cathode displacement for the specimens were 5 mm, 10 mm, and 20 mm. Specimens were immersed in a solution of NaCl 3.5 % and treated by wet-dry cycle. Profometer 5 + was used to find the location of reinforcement without damaging the surface of the concrete. Half-cell potential digital meters was used to measure the corrosion potential value of steel reinforcement. The corrosion potential measurements after 12 weeks of wet-dry cycle shows that the most negative corrosion potential was obtained for 10 mm anode-cathode displacement, i.e-391 mV. While for 5 mm and 20 mm anode-cathode displacements were -374 mV and -378 mV. Therefore, the anode-cathode displacements might affect the distribution of corrosion potential on reinforced concrete cathodic protection system.